METHODOLOGICAL PRINCIPLES OF USING THE IDEAS OF BUKHARA NOVELTY IN FORMING TOLERANCE IN YOUNG PEOPLE - Salоkhov, Akmal Qamariddinovich (Educational Research in Universal Sciences, 2023)
This article analyzes the emergence of the Jadidist movement in Bukhara, their ideas on tolerance, and their views on education.